Promotion of nursing workers quality of life (QOL): managerial responsibility of nurses - Vivian Aline Mininel; Vanda Elisa Andres Felli (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Introduction - The illness rate of nursing workers, as well as the destructive factors in their work environment have been evidenced in several Brazilian research papers1,2,3,4. The nursing manager has the potential to change this reality and promote a better working quality of life (QOL) 5. Objective - To analyze actions that are directed towards the promotion of nursing workers QOL developed by managerial nurses. Methodology - This study utilized a qualitative approach based on the reference of social determination of the health-illness process. The setting was a university hospital located in the center-west region of Brazil. The study group consisted of 22 nursing workers from different units and different work shifts. Qualitative data was collected by a focus group. This study was approved by Ethics Committee of the University of Sao Paulo Nursing School and all participants gave their free informed consent. Main results - The analyzed data showed that QOL and quality of work (QOW) are strongly linked and that motivation and satisfaction for work come from the interaction and recognition with the object of work (patients), as well as with relationships established among the work team; that the exposition to diverse workloads configures a destructive health profile and its consequence is a decrease in QOL; that there are no institutional programs or actions that promote work QOL. Still, this analysis makes possible the apprehension of psychic strain suffered by nurses in general, through the changes in work context and the impact from this in the nursing workers QOL; that the changes and the strains compromise the performance of these nurses as managers of the team, promoting physical and mental strain in the fulfillment of organizational goals; that have no initiatives directed to the promotion of workers' QOL as a managerial responsibility and these are relegated to the second level due to emergency situations demanded in day-to-day work. Conclusion - This study shows that there are almost no evident proposals for promoting nursing workers' QOL or, and those which do exist, are extremely vague. It also demonstrates that this absence of institutional policies regarding this subject also affects managerial nurses, who without an organizational structure cannot perform their role as a caregiver of the nursing team consequently increasing the rate of nursing illness to them and the nursing team.